Construct validation: coping with HIV/AIDS in Primary Health Care - Révia Ribeiro Castro; Sylvia Silva de Oliveira; Illiana Rose Benvinda de Oliveira Pereira; Wenysson Noleto dos Santos; Sâmara Fontes Fernandes; Richardson Augusto Rosendo da Silva
ABSTRACT Objective: To validate the construct and measure the trustworthiness of a questionnaire aimed at assessing HIV/AIDS coping actions developed by health professionals in Primary Health Care. Method: A methodological study carried out with 397 primary health care professionals in two municipalities in the Northeast region of Brazil. The construct validity was developed by the exploratory and confirmatory factor analysis, and the reliability analyzed by the reliability and reproducibility. Results: The validation determined six factors retention that composed the six domains of the questionnaire. Internal consistency was 0.91 and quality of the confirmatory analysis adjustment was 0.998 for Goodness of Fit Index. The domains presented Kappa values between 0.833 and 0.997. Conclusions: The final questionnaire was composed of 18 items and presented feasibility of application, and potential to evaluate actions for HIV/AIDS control in Primary Health Care.